2022
DOI: 10.1093/arclin/acac007
|View full text |Cite
|
Sign up to set email alerts
|

SCAT5 Sex Differences: Normative Data, Clinical Thresholds, and Relevance for Identification of Concussion

Abstract: Objective This study evaluated sex differences in performance on the Sport Concussion Assessment Tool–5 (SCAT5) Standardized Assessment of Concussion (SAC) and in baseline SCAT5 symptom reporting. It established clinically relevant cut points for low performance on the SAC based on both reliable chance indices (RCIs) and normative performance. This study also evaluated the diagnostic utility of the sex-adjusted SCAT5 SAC for identification of suspected concussion in collegiate athletes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The 10-item word list, but not concentration (digits backward plus months in reverse), differentiated concussed and non-concussed professional hockey players within 1 day of injury 60. The 10-item word list version of the SAC composite similarly differentiated concussed collegiate athletes and controls shortly after injury 62. In both studies, SCAT5 cognitive subtests accounted for unique variance in concussion diagnosis above symptom report alone.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…The 10-item word list, but not concentration (digits backward plus months in reverse), differentiated concussed and non-concussed professional hockey players within 1 day of injury 60. The 10-item word list version of the SAC composite similarly differentiated concussed collegiate athletes and controls shortly after injury 62. In both studies, SCAT5 cognitive subtests accounted for unique variance in concussion diagnosis above symptom report alone.…”
Section: Resultsmentioning
confidence: 79%
“…One paper did show that for the 5-item word list delayed recall portion of the SCAT2, control athletes improved their performance significantly over baseline (consistent with a practice effect), whereas the concussed group did not show an improvement 20. One paper found that using SCAT5 SAC reliable change metrics improved diagnostic sensitivity over the use of normative data alone62 and another study applying machine learning algorithms found that using SAC baseline data outperformed the use of SAC normative cut-offs when classifying athletes diagnosed with concussion 55…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…18,19 Another component of the Sports Concussion Assessment Tool–5 assesses neurocognitive function through a battery of memory tasks as a useful way to screen for concussion by using sex-specific normative data. 20 Further, shorter sleep duration acutely postconcussion has been previously associated with worsened reaction times, 21 potentially implying a connection between sleep problems and both motor and cognitive impairment following concussion. Exploring the relationship among postconcussion postural instability, cognitive function, and sleep problems is important because it provides an opportunity to understand the physical and mental effects of sleep problems and potential areas for intervention.…”
mentioning
confidence: 99%